Students’ Responses To The Use of ‘Jumanlly’ Developed With Genially in Teaching Writing Skills - Faza Oktora Indayani; Anita Anggareni; Ratih Inayah (PROJECT (Professional Journal of English Education), 2026)
Writing remains one of the most difficult English skills for Indonesian Senior High School students due to limited vocabulary, grammatical difficulties, and low motivation. This study aimed to develop “Jumanlly”, a digital learning medium using Genially, and to investigate eleventh-grade students’ responses toward it. This Research and Development (R&D) study followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The product was developed to teach the expression of giving opinions, agreeing, and disagreeing in writing. The study involved nineteen eleventh-grade students at SMA KARTIKA XIX-4 CIMAHI. Data were collected through expert validation sheets, field notes, student interviews, and teacher interviews, and analyzed qualitatively.The results showed that “Jumanlly,” an interactive game-based medium inspired by the Jumanji concept and containing a hundred writing tasks, was successfully developed. Expert validation indicated high feasibility with strong scores across all components, including learning objectives, material selection, and task design. Field trials demonstrated good practicality in classroom settings. Students’ responses were highly positive. They found the product fun, engaging, and helpful for practicing writing.In conclusion, “Jumanlly” using the Genially platform received strong positive perceptions from students and was considered practical and acceptable as an alternative medium for teaching writing skills to eleventh-grade students.